2018
DOI: 10.1177/1462474518795896
|View full text |Cite
|
Sign up to set email alerts
|

Public support for the death penalty in a red state: The distrustful, the angry, and the unsure

Abstract: Set against the backdrop of Nebraska's 2015 legislative repeal of the death penalty and the 2016 electoral reinstatement, we examined public support for capital punishment. Using two years of statewide survey data, we compared respondents who preferred the death penalty for murder, those who preferred other penalties, and those who were unsure, a respondent group often excluded from research. To understand what distinguishes among these groups, we examined media consumption, instrumental and expressive feeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Similar religious, economic, and moral reasons were found among both groups of respondents on the renewal of the death penalty in Michigan (Adinkrah & Clemens, 2018). Addressing the same issue, in support of the reintroduction of the death penalty in Nebraska, Kort-Butler and Ray (2019) found that advocates of the death penalty expressed greater anger over crime and distrust of the government regarding criminal justice, but considered that the death penalty was applied more fairly, compared to other groups (Kort-Butler & Ray, 2019). Starting from the argument that supports the return of the death penalty could reflect a protest against an unreliable justice system, Peshkopia and Trahan (2020) conducted research in Albania and identified two significant predictors of population support for the return of the death penalty.…”
Section: Literature Reviewsupporting
confidence: 55%
“…Similar religious, economic, and moral reasons were found among both groups of respondents on the renewal of the death penalty in Michigan (Adinkrah & Clemens, 2018). Addressing the same issue, in support of the reintroduction of the death penalty in Nebraska, Kort-Butler and Ray (2019) found that advocates of the death penalty expressed greater anger over crime and distrust of the government regarding criminal justice, but considered that the death penalty was applied more fairly, compared to other groups (Kort-Butler & Ray, 2019). Starting from the argument that supports the return of the death penalty could reflect a protest against an unreliable justice system, Peshkopia and Trahan (2020) conducted research in Albania and identified two significant predictors of population support for the return of the death penalty.…”
Section: Literature Reviewsupporting
confidence: 55%
“…Even today, scholars have only begun to scratch the surface of how moral-altruistic concerns may shape public attitudes toward criminal justice policies. Only a few studies of policy attitudes have focused on the effects of moral beliefs (e.g., Silver 2017; Silver and Silver 2017), a handful on those of anger (Hartnagel and Templeton 2012; Johnson 2009; Kort-Butler and Ray 2018), and none on those of altruistic fear, despite its prevalence, intensity, and pronounced influence on behavior (Drakulich 2015; Warr and Ellison 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A small but growing number of studies has found that anger about crime increases retributive impulses (Bastian, Denson, and Haslam 2013), more so even than personal fear (Kort-Butler and Ray 2018; Petersen 2010). In one of the first assessments examining how anger influences attitudes toward criminal justice policy, Johnson (2009) found that, while controlling for well-established predictors of punitiveness (e.g., conservative ideology, racial resentment), angrier people were more supportive of “get tough” crime policies.…”
Section: Public Opinion On School Safety Policies: the Moral-altruistic Modelmentioning
confidence: 99%
“…Other research has shown that fear has little or no association with support for harsh policies (Johnson, 2001;Tyler & Boeckmann, 1997). Anger is another emotion that is often a reaction to criminal offending (Pickett & Baker, 2017) and has been linked to support for punitive crime policies (Hartnagel & Templeton, 2012;Johnson, 2009) and desire for retribution (Bastian, Denson, & Haslam, 2013;Kort-Butler & Ray, 2018;Petersen, 2010). Fear and anger have also been found to shape support for measures to prevent school shootings including target hardening measures (Burton et al, 2020).…”
Section: Instrumental Concernsmentioning
confidence: 99%